Corporate social responsibility practices from the employees' perspectives: a case of Malaysian higher education institution - Chan, Tak Jie; Mohd Hasan, Nurul Ain (Human Resource Management Academic Research Society, 2018)
The current study investigates university as an entity of organisation to explore their corporate social responsibility (CSR) practices. The unit of analysis in this study focused on employees in one of the research universities in Malaysia, namely Universiti Putra Malaysia (UPM). The purpose of this study is to identify the level of employees’ understanding on CSR practices as well as their perception on selected elements of CSR that prominently practised in university. A quantitative (survey) method and multistage sampling were employed in this study, whereby questionnaires were distributed to 464 UPM staff (academic and non-academic), with only 285 valid respondents. The respondents were selected from Social Science cluster faculties and Science cluster faculties. This study focuses primarily on descriptive statistics. The findings show that respondents have a high level of understanding about CSR and the three (3) specific dimensions, namely human rights, community driven, and labour rights have shown to be the CSR practices that perceived prominent by the UPM staff. Further study to replicate the research in different university context (public or private) in Malaysian to explore more on CSR practices by respective universities was suggested. Future studies also recommended that relationships between CSR, job satisfaction, and corporate reputation need to be carried out in order to see the link between those variables.